Market Mechanisme and Systematics in the Frame of Islamic Economics - Moh Alfiyan Lulu Firdaus; Fitriana Nur Rohmah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The purpose of this study is to examine mechanisms and systematics from an Islamic economic perspective. This study uses a descriptive research design with four features: direct reading, library data, and secondary sources, and is not limited by space or time. The results of the analysis explained that Malikiyah scholars limit profit-taking to a maximum of one-third of capital, while Wahbah al-Zuhaili and al-Ghazali agree that proper profits should not exceed one-third of capital. Islamic economics emphasizes the importance of spiritualism and prohibits hoarding money and consuming other people's riches for vanity. Indonesia's government intervenes in price control to protect consumers, communities, and producers. Keynesian theory suggests that government intervention is necessary to lift a country out of recession and manage social and environmental impacts. Policies for government engagement are evolving and reacting to market realities.